PARATHYROID SURGERY - WORK OF THE ENDOCRINE SURGERY DEPARTMENT OF THE CLINIC OF GENERAL AND BREAST SURGERY UKC KRAGUJEVAC Преведи - Jakovljević, Stefan (Medicinski časopis, 2024)
Objectives: The aim of our study was to present our experience in the surgical management of patients with hyperparathyroidism in a tertiary care hospital in a middle-income, resource-limited country. Methodology: The study was conducted as an observational retrospective analysis on patients who underwent parathyroidectomy at the University Clinical Center Kragujevac (UKCKG), in the period from September 2018 to September 2023. Data were collected from medical records and analyzed using descriptive statistics and appropriate tests to evaluate parameter differences. All calculations were performed using IBM SPSS Statistics for Windows, version 23.0. Results: A total of 61 parathyroidectomies were performed, of which 7 (11.5%) had complications, including 3 (4.9%) cases of seroma and 4 (6.6%) recurrent nerve paresis. Primary hyperparathyroidism was diagnosed in 90.2% of patients, while secondary hyperparathyroidism was present in 9.8% of patients. Pathohistologically, adenoma was confirmed in 72.1% of patients, while hyperplasia was diagnosed in 27.9% of patients. The analysis showed that the volume of the parathyroid gland measured by ultrasound was statistically significantly higher compared to the volume measured by the pathologist. Also, it was observed that the upper parathyroid gland was extracted more often in patients whose preoperative calcium level was higher (p=0.015). When it comes to the histological diagnosis (adenoma/hyperplasia), no statistically significant differences were observed between the groups in all observed parameters. Comparative analysis of laboratory findings before and after surgery showed a significant decrease in the levels of parathormone, calcium and vitamin D, while the decrease in phosphorus had marginal statistical significance. Conclusion: Surgical treatment of hyperparathyroidism is effective and safe. Surgeons should be adequately educated in reference institutions in order to achieve the best possible results and reduce the number of complications.